4x+3(x+2)=13

Simple and best practice solution for 4x+3(x+2)=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+3(x+2)=13 equation:


Simplifying
4x + 3(x + 2) = 13

Reorder the terms:
4x + 3(2 + x) = 13
4x + (2 * 3 + x * 3) = 13
4x + (6 + 3x) = 13

Reorder the terms:
6 + 4x + 3x = 13

Combine like terms: 4x + 3x = 7x
6 + 7x = 13

Solving
6 + 7x = 13

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 7x = 13 + -6

Combine like terms: 6 + -6 = 0
0 + 7x = 13 + -6
7x = 13 + -6

Combine like terms: 13 + -6 = 7
7x = 7

Divide each side by '7'.
x = 1

Simplifying
x = 1

See similar equations:

| xa+cx=b | | ax+xc=b | | xa+xc=b | | 4y-8=1+5y-36 | | Ax+cx=b | | 2.8=(x/5)^3 | | 43x=4x+18 | | 6x+3=7+4x | | x+4=225 | | 6*(4x-3)+20x-24x^2=14 | | x+6=258 | | 5x-4=5x+4 | | 2=3 xx1 | | ax+3=c | | 3x+5y=200.4 | | 4-3a+4=0 | | 7x-3(x+2)=4x+3 | | 2(x+5)=4x-(2x-10) | | 6x(4x-3)+20x-24x^2=14 | | 6(2-3x)=5(x+4) | | (a-b)(2a^3-ab+3b^2)=0 | | 11.5(2x-6)=4(3.5x+12) | | 3.5=2.5d+5 | | y^2+27y=0 | | x^5+6x+17=0 | | 2/3x-3/2x=1/12 | | 1/8+2/9 | | (2x+5)(x-9)= | | P=r+s-p | | x^2+36x+27= | | 4a^2-12a-7=0 | | 6-2*7=4x-6x-3 |

Equations solver categories